Antena Yagi 11 Elemen Berbentuk Lingkaran Untuk Wireless LAN Frekwensi 2,4GHz - Slamet Purwo Santoso; Miftahul Arif (JURNAL ELEKTRO, 2025)
The rapid development of wireless technology, particularly Wireless Local Area Network (WLAN), requires high-performance antennas to ensure reliable and stable data communication. Among various designs, the Yagi antenna is widely recognized for its high gain and directional radiation characteristics. However, conventional Yagi designs often face limitations in maintaining consistent signal amplification when applied to WLAN at 2.4 GHz. This research focuses on designing and realizing an 11-element circular Yagi antenna optimized specifically for 2.4 GHz applications. The proposed antenna is composed of three main parts: a driven element serving as the active dipole, a reflector to redirect and concentrate signals, and nine directors to enhance forward radiation. The methodology covers theoretical calculation of antenna dimensions based on wavelength formulas, fabrication of the prototype, and experimental performance evaluation. Measurements were carried out using an access point, WLAN USB adapter, and WirelessMon software at test distances ranging from 20 to 30 meters with concrete wall obstructions. The results show that the proposed antenna significantly outperforms a standard WLAN USB adapter. At 20 meters, the antenna achieved -66 dBm with a gain of 12 dB, while at 30 meters it maintained -87 dBm with a gain of 7 dB. Moreover, the antenna exhibits a clear directional radiation pattern with maximum amplification between 0°–20°. The novelty of this study lies in the adoption of circular-shaped elements and the 11-element configuration, which effectively enhance WLAN signal strength and coverage in obstructed environments.